Anatomical properties of kelempayan (neolamarckia cadamba) / Nursyuhada Mohd Nizam - Mohd Nizam, Nursyuhada (Faculty of Applied Sciences, 2015)
Kelempayan species or its scientific name (Neolamarckia cadamba). This species have the potential to be commercialized as a raw material in the furniture industry and paper production. However, the information about these species is still inadequate and not being fully utilized. In this study, anatomical properties and morphological characteristics are carried out. Thus, anatomical properties is only focused on the effect of different height portion of the tree (bottom, middle, and top) while two aspects are concerned in morphological characteristics on the effect of different height portion of the tree (bottom, middle, and top) and the effect of distance (from near bark to near pith). For anatomical properties, the results have shown that different height portion gave highly significant for vessel frequency and vessel diameter. Morphological characteristics consist of fiber length, fiber diameter, and lumen diameter. For the result of the effect of different height portion, there is no significant difference for fiber length but highly significant for fiber diameter and lumen diameter. Diameter of fiber and diameter of lumen decrease when the height portions of tree increase because there is formation of new wood cell at the top portion. On the other hand, the result of effect of distance, fiber length and fiber diameter have highly significant but no significant for lumen diameter. This is because near bark has a wood cell that have through the process of formation of secondary xylem.